Migration of Rhipicephalus microplus ticks among cattle - Mazzucco Panizza, Matilde Nahimé; Rossner, Maria Victoria; Signorini Porchiett, Marcelo Lisandro; Nava, Santiago (Royal Entomology Society, 2022)
The aim of this work was to quantitatively analyse the magnitude of the migration of Rhipicephalus microplus ticks among cattle under field conditions, in groups of bovines with different stocking rates. The role of this phenomenon in the epidemiology of Anaplasma marginale has been discussed. Cattle naturally infested with R. microplus (donors) and cattle non-infested with R. microplus (recipients) were clustered for 13 days into two groups with low and high stocking rates (G1 and G2 respectively). The initial prevalence of infestation (infested cattle / total cattle) was 20% in both groups. Adult migratory ticks from donor to recipient cattle were recorded by examination of the recipient cattle on days 2, 6, 9, and 13. The tick infestation rate, calculated using the Kaplan–Meier survival test, was higher in G2 (p = 0.05). The cumulative incidence on day 13 was 25% in G1 and 65% in G2, with no significant differences. The results demonstrate that migration of adults of R. microplus under field conditions occurs, in accordance with previous studies, and that its magnitude is associated with the stocking rate. These results highlight the relevance of R. microplus in the epidemiology of A. marginale through its role as a vector in the intrastadial transmission of this pathogen of cattle.